Mixing-demixing in a trapped degenerate fermion-fermion mixture - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2006)
We use a time-dependent dynamical mean-field-hydrodynamic model to study mixing-demixing in a degenerate fermion-fermion mixture (DFFM). It is demonstrated that with the increase of interspecies repulsion and/or trapping frequencies, a mixed state of a DFFM could turn into a fully demixed state in both three-dimensional spherically symmetric as well as quasi-one-dimensional configurations. Such a demixed state of a DFFM could be experimentally realized by varying an external magnetic field near a fermion-fermion Feshbach resonance, which will result in an increase of interspecies fermion-fermion repulsion, and/or by increasing the external trap frequencies. © 2006 The American Physical Society.
Keywords: Hydrodynamics; Mixtures; Natural frequencies; One dimensional; Quantum theory; Resonance; Fermion-fermion repulsion; Feshbach resonance; One-dimensional configurations; Trap frequencies; Fermions